Anti‐inflammatory and antiviral roles of hydrogen sulfide: Rationale for considering H2S donors in COVID‐19 therapy. (26th August 2020) - Citi, Valentina; Martelli, Alma; Brancaleone, Vincenzo; Brogi, Simone; Gojon, Gabriel; Montanaro, Rosangela; Morales, Guillermo; Testai, Lara; Calderone, Vincenzo
Abstract : The COVID‐19 pandemic caused by SARS‐Cov‐2 demands rapid, safe and effective therapeutic options. In the last decades, the endogenous gasotransmitter hydrogen sulfide (H2 S) has emerged as modulator of several biological functions and its deficiency has been associated with different disorders. Therefore, many H2 S‐releasing agents have been developed as potential therapeutic tools for diseases related with impaired H2 S production and/or activity. Some of these compounds are in advanced clinical trials. Presently, the pivotal role of H2 S in modulating the inflammatory response and pro‐inflammatory cytokine cascade is well recognized, and the usefulness of some H2 S‐donors for the treatment of acute lung inflammation has been reported. Recent data is elucidating several mechanisms of action, which may account for antiviral effects of H2 S. Noteworthy, some preliminary clinical results suggest an inverse relationship between endogenous H2 S levels and severity of COVID‐19. Therefore, repurposing of H2 S‐releasing drugs may be a potential therapeutic opportunity for treatment of COVID‐19. Linked Articles: This article is part of a themed issue on The Pharmacology of COVID‐19. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v177.21/issuetoc